Hume e Machiavelli: fronteiras e afinidades - Reis, Nilo Henrique Neves dos (2010)
This thesis seeks to identify the presence of Niccolò Machiavelli's thinking within David Hume's writings. Both were theorists of political realism. Since the writings of Machiavelli had been circulating in England during the eighteenth century, it is plausible to consider that the next generation following the Florentine found inspiration in new political constructions arising from their readings of Machiavelli. With regard to Hume, both Humanist and Renaissance concepts served as necessary tools with which to base his critique of the British political system. As a moderate figure in political issues, Hume disagreed with the basic characteristics of the monarchic republican model called mixed in effect in the English nation, which according to Hume, favored recurring crises, oscillating between the two forms monarchy and republic - without focusing on one in particular. This system permitted that private interests enter in juxtaposition to collective ones, through the parliamentarians. Hume works with the interpretations of the authors of his time, and deepens the political issue with his own originality. Similar to the Florentine perspective, Hume suggests the effective monarchy as the way to put an end to the deficiencies of the system. It is necessary, however, to identify certain features (human nature, history, faction, trade), because Hume did not leave these marks in an evident way. Indeed, Hume seems to disguise the conceptual itinerary that associated him to his privileged interlocutor. Nevertheless he was aware that a connection would hinder somehow, a useful reading of his writings, as a result of the prejudice and of the negative criticisms that were attached to the Italian thinker